Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1988
DOI: 10.25249/0375-7536.1988182141148
|View full text |Cite
|
Sign up to set email alerts
|

Tectônica De Nappes Na Região De Ouro Fino, Conceição Do Mato Dentro, Mg

Abstract: The region around the District ofOuro Fino (Conceição do Mato Dentro, MG) is located on the southeastern bord er of the Espinhaço mountain range, where granite-gneíssíc (Basal Com plex) and Iow grade rnetasedimentary rocks can be found (Meta sedimentary Sequences I and II). Fine to coarse c1astic rocks (phyll ítes, quar tzites, metacon glomerates) dominate in these sequences. Basic metavolcanic rocks are less frequento The rocks in this region are intensively defonned showing a strong tangenci al , with mass t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

1995
1995
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 0 publications
0
4
0
2
Order By: Relevance
“…Cristais de granada (Figura 6H) descritos como espessartita são acessórios nas amostras de ITX, e também são descritas em hematita compacta da região sul da Serra do Espinhaço (Almeida- Abreu et al, 1988;Almeida Abreu, 1993;Almeida-Abreu e Renger, 2002).…”
Section: Conclusõesunclassified
See 1 more Smart Citation
“…Cristais de granada (Figura 6H) descritos como espessartita são acessórios nas amostras de ITX, e também são descritas em hematita compacta da região sul da Serra do Espinhaço (Almeida- Abreu et al, 1988;Almeida Abreu, 1993;Almeida-Abreu e Renger, 2002).…”
Section: Conclusõesunclassified
“…A Serra do Sapo, localizada entre os municípios de Conceição do Mato Dentro e Alvorada de Minas, na região central do estado de Minas Gerais, está inserida na borda leste da Serra do Espinhaço Meridional. Essa região compreende as principais ocorrências de formação ferrífera conhecidas na Serra do Espinhaço (Knauer, 2007), abrangendo os grupos São José (Rolim, 2016) e Serra da Serpentina (Almeida Abreu, 1989;Zacchi, 2010;Chemale et al, 2012;Dossin et al, 1985;Grossi-Sad e Magalhães, 1989;Almeida-Abreu et al, 1988;Rolim e Rosière, 2011).…”
Section: Introductionunclassified
“…This formation is composed, at is base, by decametric quartzite lenses interlayerd with schist, followed by characteristically hematite-bearing, white-greenish schist, which grades to gray-silver banded phyllite, also bearing hematite and containing graphite-rich lenses. The Meloso Formation is gradually topped by the Serra do Sapo Formation (Almeida-Abreu et al, 1989), composed predominantly by banded iron formations, locally followed by discontinuous layers of dolomite at the top. Sparse lenses of quartzite, schist, phyllite and banded iron-manganese-rich rocks (Figure 9).…”
Section: Pre-espinhaço Metasedimentary Basementmentioning
confidence: 99%
“…However, within the scope of our work, it is also worth mentioning the Itapanhoacanga Formation (Almeida-Abreu et al, 1989), a member of the Mesoproterozoic Serra de São José Group (13), defined by Rolim (2016) in the region of Conceição do Mato Dentro. In similar fashion to the Meloso Formation and the Costa Sena Group, the Serra de São José Group has never been described in our study area, but has been identified in the Serpentina Range.…”
Section: Statherian and Calymmian Riftings The Serra De São José Grou...mentioning
confidence: 99%
See 1 more Smart Citation